THE EFFECT OF COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION (CASE STUDY: SECRETARIAT OF DPRD DKI JAKARTA PROVINCE) - Bosman Butarbutar; Lenny Christina Nawangsari (Dinasti Publisher, 2022)
This study objective to determine and analyze more related to the effect of work discipline and compensation on employee-performance through work-motivation as an intervening variable (case study: the secretariat of the parliament of the province of DKI Jakarta). The research method used is a quantitative research method with causal. The research population is the Employees of the Secretariat of the parliament of the province of DKI Jakarta, the status of civil servant with a total sample of 100 respondents. Methods of data analysis using SEM-PLS. And the results indicated that compensation does not significantly affect work motivation. Work discipline has a significant effect on work motivation. Compensation does not have a significant leverage on employee performance. Work discipline has a significant effect on employee performance. Work motivation has a significant impact on employee performance. Work motivation has no impact in mediating compensation on employee performance. However, work motivation is influential in mediating work discipline on employee performance.